Intangible Cultural Heritage in the Context of Studies of Social Contacts and Networks - Drápala, Daniel (Studia Etnologiczne i Antropologiczne, 2020)
This article discusses the use of the concept of social capital in relation to the elements of intangible cultural heritage (ICH) and the need to protect it. At the outset, the author examines theoretical concepts which researchers have employed, in past decades, outside the area of ethnological studies. The article highlights one of the basic principles, that of social capital, which consists in sharing real and potential sources, knowledge, and information, which an individual person or group acquires through relations that may to some degree be characterized as institutional. Based on experiences gathered both in a national context (the Czech Republic) and within that of an international organization (UNESCO), the article attempts to assess the extent to which it is possible to apply the theoretical foundations of the idea of the social capital to ICH, where the principles of the sharing of and mutual respect towards cultural elements are two of the basic premises.